Pengaruh Kecerdasan Spiritual, Emosional dan Inelektual Terhadap Pemahaman Akuntansi - Ni Ketut Arunika Brahmantari; Herawati Khotmi; Rusdi (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2024)
This research aims to find empirical evidence about the influence of spiritual intelligence, emotional intelligence and intellectual intelligence on accounting understanding. The variables in this research consist of 3 (three) independent variables, namely spiritual intelligence (X1), emotional intelligence (X2) and intellectual intelligence (X3) and the dependent variable, namely accounting understanding (Y). The population of this study were undergraduate students majoring in accounting at STIE AMM Mataram who had taken several core courses such as introduction to accounting I, introduction to accounting II, financial accounting I, financial accounting I, advanced financial accounting II and accounting theory. The sampling technique used was purposive sampling. The criteria were based on undergraduate students majoring in accounting who had taken several core courses such as introduction to accounting I, introduction to accounting II and so on so that the number of respondents selected was 98 people. Data was obtained by distributing 98 questionnaires, of which 86 questionnaires were returned and could be used. Data were analyzed using Multiple Linear Regression. The results of this research indicate that spiritual intelligence and emotional intelligence do not have a significant positive effect on the accounting understanding variable. Meanwhile, intellectual intelligence has a significant positive effect on accounting understanding